2022
DOI: 10.1155/2022/6202457
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation of Presacral Tumour Recurrence with Tumour Metastasis and Long-Term Tumour Recurrence Risk in Patients with Rectal Cancer

Abstract: Objective. To explore the risk factors that affect long-term presacral tumour recurrence in patients with rectal cancer (RC) after radical rectal cancer resection. Methods. In our study, a total of 50 patients with presacral tumour recurrence after radical resection of RC in our hospital between May 2017 and May 2018 were enrolled in the observation group, and the other 50 patients without presacral tumour recurrence after the resection over the same span were enrolled in the control group. The two groups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%